E-learning: Digital class notes - Jere, Priscilla; Stanton, Theresa (Technical Centre for Agricultural and Rural Cooperation, 2011)
The Educational Support Network in Zambia enables teachers to use ICTs to produce locally relevant digital lesson notes for distribution to other schools in the country.